Stigmatization of HIV/AIDS patients in the context of indigenous healers and spiritual faith healers in Limpopo Province. - Lesolang, Gladys Nkele (My University, 2010)
The role of indigenous healers and spiritual faith healers in managing various conditions of ill-health has been studied and debated. The aim of this study was to determine how indigenous healers and spiritual faith healers understand and define HIV/AIDS stigma and to explore the role that indigenous healers and faith healers play in reducing or reinforcing HIV/AIDS stigma in their communities. In this study, a qualitative approach and in particular, the grounded theory methodology was used. Grounded theory is described as a research method in which theory is developed from data, rather than the other way round. The application of this methodology included personal interviews with thirty-nine practising indigenous healers and spiritual faith healers in the Limpopo Province, while additional information was gleaned from the literature review. The researcher focused on the participants‟ conceptualisation of HIV stigma, from the context of the African world view in order to gain insight into their roles as healers. The findings indicate that indigenous healers‟ cultural beliefs prevented them from having a deeper understanding of HIV stigma when compared to the faith healers. Indigenous healers were generally found to have a positive attitude towards People Living with HIV/AIDS (PLWA), while spiritual faith healers showed a less positive attitude towards PLWA. The study further found that „HIV secrecy clause‟ contained in the South African National Policy on HIV/AIDS for Learners and Educators (August 1999) prevents traditional and spiritual faith healers, the affected and infected, the family and society at large from disclosing the HIV status of those infected. It is suggested that the tendency not to disclose has the potential to encourage stigmatization and discrimination whilst at the same time hindering efforts to find solutions to the problem. The study is concluded by suggesting that HIV testing must be compulsory for every person who consults in a hospital. Such a policy move could contribute positively in terms of health promotion.
Thesis (PhD)--University of Limpopo, 2010.
Keywords: HIV/AIDS; Indigenous healers; Spiritual faith healers; 362.1969792; Psychology